Biliary stent migration causing perforation of the caecum and chronic abdominal pain. (10th September 2013) - Jones, Michael; George, Bethan; Jameson, John; Garcea, Giuseppe
Abstract : We report a case of biliary stent migration causing perforation of the caecum and presenting as chronic abdominal pain. The case was managed by colonoscopic removal of the stent.